2016
DOI: 10.1177/0004865815620703
|View full text |Cite
|
Sign up to set email alerts
|

How the prison-to-community transition risk environment influences the experience of men with co-occurring mental health and substance use disorder

Abstract: Previous research has established that people with severe mental illness and co-occurring substance use disorder leaving prison have multiple and complex health, social and economic challenges. How the criminal justice and mental health systems influence the individual prisonto-community transition experience of this population is less well understood. This paper draws on unique qualitative data from a study of 18 men with co-occurring severe mental illness and substance use disorder leaving prison in Queensla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 55 publications
0
22
0
1
Order By: Relevance
“…The results of this study were found to be in line to studies on mental illness stigma and discrimination in Zambia, Tanzania and Australia, that documented community perception and knowledge on the causes of mental illnesses are caused by evil spirits; substance, drug and alcohol abuse. [7][8][9] A study on co-morbidity of substance misuse and mental illness in a community also reported a higher prevalence of psychiatric disorders among alcohol addicts. [10][11][12] The study results also showed 40.4% of the respondents either strongly disagreed (14.2%) or disagreed (26.2%), but 33.3% and 8.5% were agreed and strongly agreed that mental illness is genetically inherited disease, this indicates poor knowledge and perception on its inheritance among the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were found to be in line to studies on mental illness stigma and discrimination in Zambia, Tanzania and Australia, that documented community perception and knowledge on the causes of mental illnesses are caused by evil spirits; substance, drug and alcohol abuse. [7][8][9] A study on co-morbidity of substance misuse and mental illness in a community also reported a higher prevalence of psychiatric disorders among alcohol addicts. [10][11][12] The study results also showed 40.4% of the respondents either strongly disagreed (14.2%) or disagreed (26.2%), but 33.3% and 8.5% were agreed and strongly agreed that mental illness is genetically inherited disease, this indicates poor knowledge and perception on its inheritance among the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Related to this, transitions of incarcerated men back to the community have attracted some research attention. Highlighted have been the high rates of prisoner’s comorbidities and their lack of financial and social capital for garnering effectual health help-seeking and/or self-care in transitioning back to community life ( Denton, Foster, & Bland, 2017 ). An array of challenges including psychiatric symptoms, substance use, past criminal history, emotional conflicts can increase the risk of recidivism ( Barrenger, Draine, Angell, & Herman, 2017 ).…”
Section: Masculinities and Men’s Mental Health In And Out Of Prisonmentioning
confidence: 99%
“…The aforementioned complex mental health issues have resulted in calls for reform and development of prison-to-community transitions as well with support services to promote the well-being of men in custody ( Denton et al, 2017 ; Fazel, Hayes, Bartellas, Clerici, & Trestman, 2016 ). The purpose of the current study and article was to describe the connections between masculinities and men’s mental health among prisoners transitioning into and out of a Canadian federal correctional facility.…”
Section: Masculinities and Men’s Mental Health In And Out Of Prisonmentioning
confidence: 99%
“…The stresses of reintegration include financial hardship, difficulties accessing housing, stigma and mental and physical health issues [38]. Further, ex-prisoners are often re-exposed to the environment that led them to offend, including potential exposure to illicit drugs, tobacco and alcohol [39]. This is reflected in elevated rates of post-release mortality, especially for Indigenous ex-prisoners, including as a result of alcohol consumption [7,8].…”
Section: Discussionmentioning
confidence: 99%